Optimal site selection for the installation of solar PV plants: a case study in Nakhchivan Ar, Azerbaijan (Journal of Geography and Environmental Management, 2021)
Since the electrical power produced by converting total solar radiation on a horizontal surface, composed of direct and diffuse components of PV cells, has low output power, it is necessary to identify areas with high power factor for more efficient power generation. However, due to the low efficiency of PV panels (14-18%) and the low intensity of total solar radiation on a horizontal surface, large installation space is required to achieve a certain power level. Due to the high cost of installing solar power plants, a comprehensive systematic assessment of the geographic factors of the region is required to select the most suitable location. The reason we chose Nakhchivan as the study area is that the radiation level is high compared to other regions of Azerbaijan (1220-1699 kWh/m2-year), and the number of hours of sunshine per year exceeds 2500. Since the creation of solar power plants in regions with high values of the total radiation on a horizontal surface depends on technical, economic and environmental criteria, descriptive criteria are used to determine the optimal areas. The analytical hierarchy process model, based on multi-criteria decision-making methods, was used to identify suitable locations for solar power plants. In the first phase of the study, seven criteria were analysed to determine suitable locations: Total solar radiation on a horizontal surface, slope, and land use, buffer distance from areas with high annual solar energy potential to residential areas, proximity to substations, highways, and power lines. At the second stage, the level of accessibility and suitability of areas within the framework of certain criteria was determined using the weighted overlay tool in geographic information systems. At the second stage, using the weighted overlay tool in GIS, the level of suitability of territories was determined according to certain criteria. As a result, the study, it was concluded that 9.5% (510 km2) of the land of Nakhchivan have high suitability, 12% (645 km2) - average suitability and 24% (1290 km2) - low suitability for placing solar power plants. The remaining 54.5% (2930 km2) of the region belongs to the territories that are not suitable for use due to low radiation, high slope, the presence of protected areas, settlements, agricultural areas and poorly developed infrastructure. Optimal locations cover mainly the southern and eastern parts of the region, as shown in the polygon shape on the suitability map. The electricity generated by converting full solar radiation to the horizontal surface consists of direct and diffuse components of PV cells, which, due to their low output power, can be used in areas with high energy efficiency for efficient power generation.
Keywords: renewable energy sources, solar energy, geographic information systems, analytical hierarchy process, site selection.